Fatores que influenciam a saúde mental de mulheres usuárias de Centros de Atenção Psicossocial (CAPS): uma revisão narrativa - Ianuci, Larissa Mascarin (Universidade Federal de São Carlos)
The understanding of women's mental health transcends the traditional boundaries of gender studies, expanding into an approach that recognizes the complexity of female identities, identifying how factors such as social class, race, sexual orientation, and many other elements interact to shape individual experiences. In the context of CAPS (Psychosocial Care Centers), understanding these factors is essential to identify the specific challenges faced by women, which include not only clinical aspects but also social and gender dimensions that affect their mental health. This Course Conclusion Work aimed to investigate and understand the factors that influence the mental health of women users of Psychosocial Care Centers (CAPS). This is a Narrative Literature Review, conducted based on searches in the BVS, Scielo, and CAPES Periodicals Portal databases using the following descriptor combinations: "women AND CAPS AND mental health"; "women AND CAPS AND psychological distress" and "women AND CAPS". At the end of the searches, reading process, and analysis of the studies, the review was composed of 10 articles, which were organized into three categories for discussion, namely: 1) Mental Health and Gender; 2) Psychoactive Substance Dependence and Social Vulnerabilities; and 3) Impacts of Work and Precarization on Mental Health. The results highlighted that female psychological distress is deeply linked to gender inequalities, violence, overload of social roles, and the persistence of stigmas and social barriers. It was found that the professionals' approach in CAPS services must go beyond symptoms, recognizing the social dimensions and the intersection of factors such as race, class, and sexual orientation that accentuate the users' psychological vulnerability. It is concluded that understanding these factors is essential for CAPS practices to become more sensitive and inclusive, questioning the asylum logic and deterministic models, promoting more equitable and effective support for women.
Factors influencing the mental health of women using Psychosocial Care Centers (CAPS): a narrative review
Keywords: Mulheres; Sofrimento psíquico; Saúde mental; Centro de Atenção Psicossocial; Women; Psychological distress; Mental health; Psychosocial Care Center; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar